Rapid Development of Perceptual Gaze Control in Hearing Native Signing Infants and Children - Bosworth, Rain G. (Dev Sci, 2021)
Children’s gaze behavior reflects emergent linguistic knowledge and real-time language processing of speech, but little is known about naturalistic gaze behaviors while watching signed narratives. Measuring gaze patterns in signing children could uncover how they master perceptual gaze control during a time of active language learning. Gaze patterns were recorded using a Tobii X120 eye-tracker, in 31 non-signing and 30 signing hearing infants (5-14 months) and children (2-8 years) as they watched signed narratives on video. Intelligibility of the signed narratives was manipulated by presenting them naturally and in video-reversed (“low intelligibility”) conditions. This video manipulation was used because it distorts semantic content, while preserving most surface phonological features. We examined where participants looked, using linear mixed models with Language Group (non-signing vs. signing) and Video Condition (Forward vs. Reversed), controlling for trial order. Non-signing infants and children showed a preference to look at the face as well as areas below the face, possibly because their gaze was drawn to the moving articulators in signing space. Native signing infants and children demonstrated resilient, face-focused gaze behavior. Moreover, their gaze behavior was unchanged for video-reversed signed narratives, similar to what was seen for adult native signers, possibly because they already have efficient highly focused gaze behavior. The present study demonstrates that human perceptual gaze control is sensitive to visual language experience over the first year of life and emerges early, by 6 months of age. Results have implications for the critical importance of early visual language exposure for deaf infants.